IMMUNOCHEMICAL STUDIES OF 22S PROTEIN FROM ISOLATED MITOTIC APPARATUS - Bibring, Thomas (The Rockefeller University Press, 1969)
Evidence is presented that the "22S protein" of mitotic apparatus isolated from sea urchin eggs is not microtubule protein. An antibody preparation active against 22S protein is described, and immunochemical studies of the distribution of 22S protein in various cellular fractions and among morphological features of mitotic apparatus are reported. The protein is ubiquitous in the metaphase egg fractions that were tested but is not found in sperm flagella. It is immunologically distinct from proposed microtubule protein isolated from mitotic apparatus by the method of Sakai, and from proposed microtubule protein obtained after extraction with mild acid. It exists in nontubule material of isolated mitotic apparatus but is not detectable in microtubules.